International Bullous Diseases Group: consensus on diagnostic criteria for epidermolysis bullosa acquisita. (8th May 2018) - Prost‐Squarcioni, C.; Caux, F.; Schmidt, E.; Jonkman, M.F.; Vassileva, S.; Kim, S.C.; Iranzo, P.; Daneshpazhooh, M.; Terra, J.; Bauer, J.; Fairley, J.; Hall, R.; et al.
Summary: Background: Epidermolysis bullosa acquisita (EBA) is a complex autoimmune bullous disease disease with variable clinical presentations and multiple possible diagnostic tests, making an international consensus on the diagnosis of EBA essential. Objectives: To obtain an international consensus on the clinical and diagnostic criteria for EBA. Methods: The International Bullous Diseases Group (IBDG) met three times to discuss the clinical and diagnostic criteria for EBA. For the final voting exercise, 22 experts from 14 different countries voted on 50 different items. When > 30% disagreed with a proposal, a discussion was held and re‐voting carried out. Results: In total, 48 of 50 proposals achieved consensus after discussion. This included nine diagnostic criteria, which are summarized in a flow chart. The IBDG was unable to determine one procedure that would be applicable worldwide. A limitation of the study is that differential diagnosis of bullous systemic lupus erythematosus has not been addressed. Conclusions: This first international consensus conference established generally agreed‐upon clinical and laboratory criteria defining the clinical classification of and diagnostic testing for EBA. Holding these voting exercises in person with the possibility of discussion prior to voting has advantages in reaching consensus over Delphi exercises with remote voting. Abstract : What's already known about this topic? Currently, there is a lack of consensus on the diagnosis of epidermolysis bullosa acquisita (EBA). What does this study add? These recommendations, which have been developed by international experts, provide appropriate pathways for EBA diagnosis: the algorithms may be used to distinguish EBA from other blistering diseases, which affect the epithelial basement membrane zone. Linked Comment:  Yamagami. Br J Dermatol 2018;179 :7 .